The Effect of AI-Based Musicalized Media on Motivation and Learning Outcomes in Social Studies - Rohadi Eko Sutanto; Endah Andayani; Roni Alim Ba’diya Kusufa (ASANKA : Journal of Social Science and Education, 2026)
AI-based musicalization media were developed as an alternative learning method that integrates social studies material in the form of songs, supported by artificial intelligence technology. The purpose of this study was to determine the effect of AI-based musicalization media on students' motivation and learning outcomes at SMPN 1 Donomulyo. This study was motivated by the suboptimal use of interactive learning media, which led to low student motivation and learning outcomes. The study used a quantitative, nonequivalent control-group design. The research subjects were students of class IX A as the experimental class and class IX B as the control class. Data were collected using a learning motivation questionnaire and an essay test on social studies learning outcomes, and analyzed using a MANOVA. Based on the Multivariate Test table, an F value of 45.562 was obtained, with a p-value of 0.000 (< 0.05). Therefore, it can be concluded that AI-based musicalization media have a simultaneous effect on students' motivation and social studies learning outcomes. This finding confirms that AI media is recommended as an alternative social studies learning method in line with the development of educational technology.